Butylphthalide reduces plaque burden and improves neurological function in carotid atherosclerotic disease: a pooled analysis - Yang, Jia; Pei, Xinhao; Qiang, Jianxin; Li, Lijuan; Liu, Yanping; Hao, Panpan (Frontiers in Pharmacology, 2025)
BackgroundThe influence of butylphthalide on atherosclerotic plaque burden remains underexplored. This pooled analysis was aimed to evaluate its efficacy and safety in carotid atherosclerosis.MethodsThe literature were retrieved in online databases. Carotid intima-media thickness (IMT), plaque size, Crouse score, National Institute of Health Stroke Scale (NIHSS), circulating biomarkers, and drug-related adverse events were extracted and compared between the butylphthalide group and the control group without butylphthalide.ResultsNine randomized controlled trials with 892 subjects were included. Compared with the control group, butylphthalide significantly reduced carotid IMT (MD -0.24 mm, 95% CI [-0.31, −0.16], P < 0.00001), plaque size (MD -3.83 mm2, 95% CI [-5.64, −2.01], P < 0.0001), Crouse score (MD -0.48, 95% CI [-0.89, −0.08], P = 0.02), hs-CRP (MD -1.65 mg/L, 95% CI [-2.99, −0.30], P = 0.02) and MMP-9 (MD -12.29 μg/L, 95% CI [-16.24, −8.33], P < 0.00001). Neurological improvement (NIHSS reduction: MD -2.94, 95% CI [-4.15, −1.73], P < 0.00001) and comparable safety profiles (OR 0.93, 95% CI [0.37, 2.37], P = 0.89) were observed.ConclusionButylphthalide treatment reduces carotid plaque burden, improves neurological recovery and has a high safety profile, supporting its role in stroke prevention.